Frequency of Depression in Patients with Type 2 Diabetes Mellitus and its Relationship with Glycemic Control and Diabetic Microvascular Complications - Sharif, Sabira (Cureus, 2019)
Introduction Various clinical studies have reported that clinical depression is a common co-morbidity in patients with type 2 diabetes mellitus. Depression can badly affect the lifestyle of diabetic patients and impair the proper management of diabetes mellitus. Therefore, there exists a need to identify risk factors of depression in diabetic patients especially in relation to various clinical parameters, glycemic control and diabetic microvascular complications. Materials and methods It was a cross-sectional study conducted in a tertiary care hospital in Pakistan from August 2018 to April 2019. We recruited type 2 diabetic patients and measured their various clinical and hematological parameters. We evaluated depression using Patient Health Questionnaire (PHQ-9) and evaluated its relationship with glycemic control, duration of diabetes, fasting lipid profile and presence of various diabetic microvascular complications. Results There were 100 subjects in the study having a mean age 58.3 ± 12.4 (range: 36 - 71) years with a male to female ratio of 1:1.2. The mean duration of type 2 diabetes mellitus was 11.2 ± 9.2 years. The mean PHQ-9 score of the study population was 10.2 ± 8.1. The frequency of depression was found to be 40.0%. Depression was most frequently found in women and in patients between 40 to 60 years of age (60.0%). Depression was more common in patients with dyslipidemia (p-value = 0.0015). Patients with diabetic retinopathy, diabetic nephropathy and diabetic neuropathy were 3.8 times, 4.2 times and 2.1 times more likely to have clinical depression than the patients without these complications. Patients with glycated hemoglobin (HbA1c) worse than 7.5% had a significantly higher rate of depression than those whose HbA1c ranged from 6.5 - 7.5 % (p-value = 0.0028). Duration of diabetes mellitus did not significantly affect the frequency of depression in diabetic patients. Conclusion Depression is common in a large number of diabetic patients. Female gender, dyslipidemia, diabetic microvascular complications and impaired glycemic control are significantly associated with depression in diabetic patients.